(untitled) (Journal of Libya for geographical studies, 2026)
This study examines and evaluates the dynamics of vegetation cover in the Taminah branch of Misrata Municipality over the period 1984–2024, with the aim of identifying vegetation cover classes and the changes that have occurred in terms of area and relative proportions. The study also seeks to understand the key factors influencing these changes, particularly urban expansion and climatic variations. Spatial analysis techniques were employed through the processing of satellite imagery and the application of the Normalized Difference Vegetation Index (NDVI .(The results revealed noticeable changes in vegetation cover over the study period and identified several human-induced factors that have had negative impacts on vegetation conditions. In addition, the areas most affected by these changes were clearly delineated. The study recommends the adoption of sustainable development policies to protect natural resources, along with conducting further research to enhance understanding of the impacts of climate change on the local environment.